Memori Episodik sebagai Terra Incognita yang Membatasi Neuroteknologi - Ramadhanty, Siti Azri Ulmi; Albertus, Harsawibawa (Syntax Idea, 2021)
One of the implications of the development of neuroscience is neurotechnology. Initially, neurotechnology aims to address brain dysfunction, such as overcoming Alzheimer's disorders that cause memory loss. However, neurotechnology seems to go a step further, i.e. it not only serves to repair brain damage, but also to correct mental phenomena connected to the brain or that are "produced" by the brain, which are associated with memory. Based on this, the question arises, whether it is possible that neural technology improves and replaces human memory. Nevertheless, these neurotechnical efforts seem to ignore the meaning of memory itself, including what actually "builds" memory, so that humans can have different feelings of memory. Thus, to answer this problem, the author first interprets memory explicitly through a clear difference between semantic memory and episodic memory, to show that human memory, which is an episodic memory, is associated with qualitative states. Second, by describing the opportunities presented by neurotechnology through mind experimentation regarding neuron replacement by electronic chips, to demonstrate the impossibility of neurotechnology functioning in the same way as neurons in the brain that produce episodic memory with these qualitative states. Therefore, based on these arguments, it will be known that neurotechnology is actually impossible to improve, especially replacing human memory.